Geopolitical bodies: media discourse on the Indonesian national identity - Sri Utomo, Muhammad Ridhlo Al Qodri (Penerbit Universiti Kebangsaan Malaysia, 2020)
The paper examines how Indonesian media contested for the Indonesian national identity, from the period of National Awakening (1908) to the period of Sukarno’s Guided Democracy (1957-1965), focusing on the issue of human body constructions. The paper is based on qualitative discourse analysis, applying Norman Fairclough’s discourse method, especially the analysis of discourse practices and social changes. The data were collected from several media, such as books, newspapers, and advertisements in the periods being studied. The study finds that the national identity contestations involved the struggle to construct and discipline the human body, which was influenced by traditional Javanese culture, Dutch imperialism, Japanese occupation, and national independence spirits. In the Javanese culture, the body is perceived as a sacred site, while the Dutch colonialism has transformed this idea of sacred and collective bodies to the more secular and individualized bodies. The Japanese occupation has totally mobilized the human body into a collective single identity. After independence, the human body discourse was closely related to the geopolitical tensions between nationalist (Javanese) and modernist (non-Javanese) discourses. The nationalist suggested that Indonesia needs to form a collective physical identity for nation-building, while the modernist suggested accommodating cosmopolitanism and individualism to build a national identity. The contestations for Indonesian national identity were not complete until 1965, which has also triggered the crisis of national unity in the middle of the 1960s. The study also concludes that the discourse of the human body was very important in the debate of Indonesian national identity.